Competitive support of governments for research, development and innovation and its interaction with knowledge production criteria - Shahram Gilaninia (Cogent Business & Management, 2017)
This study tends to examine effect of support given by government and other private institutions to research, development and innovation on knowledge production criteria. In the contemporary world, research, development and innovation are key factors for improving economic performance and social welfare. Governments which tend to take advantage of this approach need to adopt correct and tested strategies and eliminate limitations in allocating resources to driving factors of innovation process. In this regard, this study addresses various forms of support given by government and private sector to R&D; by analyzing and evaluating effects of these supports on knowledge production criteria, this study tends to rank supportive approaches to research and development in the most industrialized and newly industrialized countries. As the results showed, statistics and ranking of countries in terms of their support for knowledge production are not enough for management and operation of knowledge production and most importantly GNP; thus, it cannot provide necessary information for this matter.
Keywords: 650